Explaining the Effect of Crop-Raiding on Food Security of Subsistence Farmers of KwaZulu Natal, South Africa - Raphela, Tlou D.; Pillay, Neville (Frontiers in Sustainable Food Systems, 2021)
Across the globe, crop-raiding has been known to have a significant impact on subsistence farmers livelihoods in developing countries. However, the relationship between crop-raiding and food security of small-scale farmers is not well-studied. We investigated the effects of crop-raiding on homestead food security of a subsistence farming community on the edge of the Hluhluwe Game Reserve in northern KwaZulu-Natal Province, South Africa. We analyzed the relative calories lost to important food security crops (maize, common bean, spinach, and beetroot) damage by crop raiders. In addition, we conducted questionnaire surveys of resident farmers and conservationists of the Hluhluwe Game Reserve to explain the effect of crop-raiding on food security. We firstly assessed how crop loss influenced relative calorie loss as an indicator of food security by comparing relative calorie loss with two predictors of food security: homestead size and contribution of crops to the farmers' food basket. Larger homesteads were more prone to food insecurity as compared to smaller households as they experienced higher calorie loss, especially in terms of maize (Zea mays), the most important food security crop in South Africa. This was because maize contributed the highest (91–100%) to the homestead food basket of these farmers. Secondly, we assessed farmers and conservationists' perceptions and opinions on crop-raiding issues. Farmers reported maize as the crop most damaged by crop-raiding animals. Conservationists reported crop-raiding with other major problems in and around the Reserve; this showed that conservationists acknowledge the issue of crop-raiding as a problem for subsistence farming communities abutting protected areas. Both farmers and conservationists reported insects as the most damaging crop raider. Our study suggests that larger homesteads, particularly where maize contributes substantially to homestead food baskets, are more prone to food insecurity in the rural subsistence farming community that we studied. In concordance with many studies, insects were reported as the culprits by both farmers and conservationists. Small, ubiquitous animals, such as insects are reported to cause much crop damage where they occur. The findings of our study suggest that the food security of the studied farmers is threatened by crop-raiding.